Effect of Enamel Bonding Agents on Pit and Fissure Sealant Retention in An Isolated Situation - Z. Jaberi Ansari (Journal of Dentistry of Tehran University of Medical Sciences, 2008)
Objective: The aim of this study was to evaluate the efficacy of enamel bonding agents on pit and fissure sealant retention in a well-isolated situation.Materials and Methods: Thirty-two patients (6-9 years old, all males) with four fully erupted permanent first molars were selected. Their occlusal, buccal, and lingual fissures were sealed according to a split-mouth design using concise light curing white sealant (3M) for the control group and Heliobond (Vivadent) plus sealant for the study group. The retention of sealants was carefully inspected after one year and the data were analyzed by chi-square test.Results: The percentages of complete retention in the study and control groups were 73.2, and 71.4, respectively. Chi-square test revealed no significant difference between these groups (P>0.05)Conclusion: In a dry and isolated situation, application of enamel bonding agent has no significant effect on fissure sealant retention.